Auditory, Visual, and Cross-Modal Temporal Processing Skills Among Chinese Children With Developmental Dyslexia. (November 2019) - Liu, Sisi; Wang, Li-Chih; Liu, Duo
The present study examined whether temporal processing (TP) is associated with reading of a non-alphabetic script, that is, Chinese. A total of 126 primary school–aged Chinese children from Taiwan (63 children with dyslexia) completed cross-modal, visual, and auditory temporal order judgment tasks and measures of Chinese reading and literacy-related skills. The results showed that typically developing children and children with dyslexia differed in all TP skills. Structural equation modeling indicated that cross-modal TP contributed independently to character recognition in the entire sample if the significant effects of phonological awareness, orthographic knowledge, and rapid automatized naming were considered. The multi-sample analysis showed that TP did not predict reading in the typical group after controlling for literacy-related skills, but visual and cross-modal TP skills independently contributed to reading in the group with dyslexia in addition to literacy-related skills. Finally, the path analysis indicated that in the typical group, separate TP skills affected reading through literacy-related skills, but visual and cross-modal TP skills had direct effects on character reading in the group with dyslexia. These findings suggest that TP is more important for reading in children with dyslexia than in typically developing children, and the roles of TP in dyslexia require further examination.